Reading Poetry and Prose: Eye Movements and Acoustic Evidence. Issue 3 (16th March 2022) - Blohm, Stefan; Versace, Stefano; Methner, Sanja; Wagner, Valentin; Schlesewsky, Matthias; Menninghaus, Winfried
ABSTRACT: We examined genre-specific reading strategies for literary texts and hypothesized that text categorization (literary prose vs. poetry) modulates both how readers gather information from a text (eye movements) and how they realize its phonetic surface form (speech production). We recorded eye movements and speech while college students ( N = 32) orally read identical texts that we categorized and formatted as either literary prose or poetry. We further varied the text position of critical regions (text-initial vs. text-medial) to compare how identical information is read and articulated with and without context; this allowed us to assess whether genre-specific reading strategies make differential use of identical context information. We observed genre-dependent differences in reading and speaking tempo that reflected several aspects of reading and articulation. Analyses of regions of interests revealed that word-skipping increased particularly while readers progressed through the texts in the prose condition; speech rhythm was more pronounced in the poetry condition irrespective of the text position. Our results characterize strategic poetry and prose reading, indicate that adjustments of reading behavior partly reflect differences in phonetic surface form, and shed light onto the dynamics of genre-specific literary reading. They generally support a theory of literary comprehension that assumes distinct literary processing modes and incorporates text categorization as an initial processing step.